Service in the State Bureau of Investigation of Ukraine bodies as a type of public service - O. M. Didenko; O. Yu. Salmanova (Law and Safety)
Public service in the bodies of the State Bureau of Investigation of Ukraine has been defined as the main mechanism of these bodies functioning, which is manifested in the multifaceted activities of the staff and employees of the Bureau. The application of the laws of Ukraine “On the State Bureau of Investigations” and “On the State Service” regarding service in the bodies of the State Bureau of Investigations of Ukraine has been analyzed. It has been concluded that the service in the bodies of the State Bureau of Investigation of Ukraine is a derived concept from the civil service in Ukraine.